The Optimization of Sulphide Oxidizing Bacteria (SOB) for Oil Corrosivity Reduction at Indramayu Coast, The Northern Coastal Area of West Java - Yudi Nurul Ihsan; Kalysta Fellatami; Rega Permana; Jiang Mingguo; Tri Dewi Kusumaningrum Pribadi (Jurnal Ilmiah Perikanan dan Kelautan)
Highlight Research